The Story of Equine Atypical Myopathy: A Review from the Beginning to a Possible End. (14th November 2012) - Votion, Dominique-Marie
Abstract : Atypical myopathy (AM) is a frequently fatal seasonal pasture myopathy that emerges in Europe. Outbreaks are of an acute and unexpected nature and practitioners should be prepared to handle these critically ill patients. This review retraces the history of AM and describes results of epidemiological investigations that were conducted to raise hypotheses concerning the etiology of this devastating disease as well as to be able to suggest potential preventive measures. Also, clinical studies have contributed to a better definition and recognition of the syndrome, whereas elucidation of the pathological process, identified as a multiple acyl-CoA dehydrogenase deficiency (MADD), was a great step forward improving medical management of AM and guiding the search for the etiological agent towards toxins that reproduce the identified defect. Treatment plans can be extrapolated from the described clinical signs and metabolic problems, but they remain limited to supportive care until the causative agent has been identified with certainty. Since treatment is still unsuccessful in the majority of cases, the main emphasis is currently still on prevention. This paper aims at being a practical support for equine clinicians dealing with AM and is based on discussion and comparison of the currently available scientific data.